1985
DOI: 10.1055/s-2007-1001959
|View full text |Cite
|
Sign up to set email alerts
|

Von der Familientherapie zur Angehörigenarbeit oder vom therapeutischen zum präventiv-rehabilitativen Paradigma in der Schizophreniebehandlung

Abstract: Although family therapy (or family psychotherapy) originated from schizophrenia research and therapy, it seems to be labouring particularly under the difficulties presented by schizophrenia; in the author's opinion this is due to an epistemological error. A promising new approach has emerged in recent years, once again originating from schizophrenia research, namely, "family education" or co-operation with closest relatives of the patient. The present article compares family therapy and family education, descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
1
0
1
Order By: Relevance
“…The project discussed here borrowed certain therapeutic and administrative tools, such as the 'soft room' and nurse's timetables (see below), from the initial Soteria experiment. The same name (a rough translation from Greek meaning safety, security, salvation) was used, despite the fact that 'Soteria Berne' differs from Mosher's approach in various ways: it is based on a medical model integrating psychosocial and biological factors, the programme is under medical supervision, and it incorporates, in addition, the following therapeutic strategies: (a) the 'educational approach' and family treatment strategy (Leff et ai, 1982;Anderson, 1983;Hubschmid, 1985) intended to establish close collaboration between family, significant others, and carers; (b) long-term after-care and relapse prevention (Hogarty, 1984;Dauwalder, 1988); (c) inducing positive expectations (Ciompi et ai, 1979) by providing everyone involved in the therapy process with clear and up-dated information about the illness, its treatment, the longterm risk of relapse, and the chance of recovery, according to follow-up studies which have demonstrated that long-term outcome is substantially more favourable and heterogenous than hitherto believed (Ciompi & Muller, 1976;Bleuler, 1978;Huber et ai, 1979); (d) administration of low and targeted medication as viable alternatives to drug-free strategies (Carpenter et ai, 1977(Carpenter et ai, , 1987(Carpenter et ai, , 1990Herz et ai, 1982;Kane et ai, 1983Kane et ai, , 1987Chiles et ai, 1989).…”
mentioning
confidence: 99%
“…The project discussed here borrowed certain therapeutic and administrative tools, such as the 'soft room' and nurse's timetables (see below), from the initial Soteria experiment. The same name (a rough translation from Greek meaning safety, security, salvation) was used, despite the fact that 'Soteria Berne' differs from Mosher's approach in various ways: it is based on a medical model integrating psychosocial and biological factors, the programme is under medical supervision, and it incorporates, in addition, the following therapeutic strategies: (a) the 'educational approach' and family treatment strategy (Leff et ai, 1982;Anderson, 1983;Hubschmid, 1985) intended to establish close collaboration between family, significant others, and carers; (b) long-term after-care and relapse prevention (Hogarty, 1984;Dauwalder, 1988); (c) inducing positive expectations (Ciompi et ai, 1979) by providing everyone involved in the therapy process with clear and up-dated information about the illness, its treatment, the longterm risk of relapse, and the chance of recovery, according to follow-up studies which have demonstrated that long-term outcome is substantially more favourable and heterogenous than hitherto believed (Ciompi & Muller, 1976;Bleuler, 1978;Huber et ai, 1979); (d) administration of low and targeted medication as viable alternatives to drug-free strategies (Carpenter et ai, 1977(Carpenter et ai, , 1987(Carpenter et ai, , 1990Herz et ai, 1982;Kane et ai, 1983Kane et ai, , 1987Chiles et ai, 1989).…”
mentioning
confidence: 99%
“…Die Gruppen mit je zwei Mitarbeitern (Professionellen) konnten von Angehörigen ± Eltern, Geschwistern, Partnern ± während und nach der stationären Behandlung genutzt werden ohne anwesende Patienten (mit einer Ausnahme bei überwiegend depressiven Patienten) Die Patienten unterstützten durchweg die Teilnahme etwa so: ¹Geh doch hin, das tut Dir gut!ª Die Angebote waren kostenlos für die Angehörigen ± abgesehen von den Fahrtkosten. Die Leiter standen grundsätzlich ¹im Rücken der Angehörigenª [11] und versuchten Wertschätzung zu zeigen. ± Die Gruppen und Angehörigentage fanden in den Räumen der Institutsambulanzen statt.…”
Section: Was Wurde Wie Vermittelt?unclassified